COVAC1 phase 2a expanded safety and immunogenicity study of a self-amplifying RNA vaccine against SARS-CoV-2. (February 2023) - Szubert, Alex J.; Pollock, Katrina M.; Cheeseman, Hannah M.; Alagaratnam, Jasmini; Bern, Henry; Bird, Olivia; Boffito, Marta; Byrne, Ruth; Cole, Tom; Cosgrove, Catherine A.; Faust, Saul N.; Fidler, Sarah; et al.
Summary: Background: Lipid nanoparticle (LNP) encapsulated self-amplifying RNA (saRNA) is well tolerated and immunogenic in SARS-CoV-2 seronegative and seropositive individuals aged 18–75. Methods: A phase 2a expanded safety and immunogenicity study of a saRNA SARS-CoV-2 vaccine candidate LNP-nCoVsaRNA, was conducted at participating centres in the UK between 10th August 2020 and 30th July 2021. Participants received 1 μg then 10 μg of LNP-nCoVsaRNA, ∼14 weeks apart. Solicited adverse events (AEs) were collected for one week post-each vaccine, and unsolicited AEs throughout. Binding and neutralisating anti-SARS-CoV-2 antibody raised in participant sera was measured by means of an anti-Spike (S) IgG ELISA, and SARS-CoV-2 pseudoneutralisation assay. (The trial is registered: ISRCTN17072692, EudraCT 2020-001646-20). Findings: 216 healthy individuals (median age 51 years) received 1.0 μg followed by 10.0 μg of the vaccine. 28/216 participants were either known to have previous SARS-CoV2 infection and/or were positive for anti-Spike (S) IgG at baseline. Reactogenicity was as expected based on the reactions following licensed COVID-19 vaccines, and there were no serious AEs related to vaccination. 80% of baseline SARS-CoV-2 naïve individuals (147/183) seroconverted two weeks post second immunization, irrespective of age (18–75); 56% (102/183) had detectable neutralising antibodies. Almost all (28/31) SARS-CoV-2 positive individuals had increased S IgG binding antibodies following their first 1.0 μg dose with a ≥0.5log10 increase in 71% (22/31). Interpretation: Encapsulated saRNA was well tolerated and immunogenic in adults aged 18–75 years. Seroconversion rates in antigen naïve were higher than those reported in our dose-ranging study. Further work is required to determine if this difference is related to a longer dosing interval (14 vs. 4 weeks) or dosing with 1.0 μg followed by 10.0 μg. Boosting of S IgG antibodies was observed with a single 1.0 μg injection in those with pre-existing immune responses. Funding: Grants and gifts from the Medical Research Council UKRI (MC_PC_19076 ), the National Institute for Health Research /Vaccine Task Force, Partners of Citadel and Citadel Securities, Sir Joseph Hotung Charitable Settlement, Jon Moulton Charity Trust, Pierre Andurand, and Restore the Earth .